The application of Scilab software in frequency mode simulation on the circular membrane - Dwi Nova Siti Handayani; Yudhiakto Pramudya; Suparwoto Suparwoto; Muchlas Muchlas (Universitas Sebelas Maret, 2018)
Scilab software is utilized for solving physics cases in two dimensional wave equations. This study aims to obtain a frequency mode simulation on the circular membrane so that it can display the wave pattern of each frequency mode. The method is to compare the simulation results with the normal mode circular membrane in each mode in to the theoretical calculation. The simulation has been done by utilizing the physics concept in a wave equation involving cos θ. The function of the wave equation is , assuming that r is the radius of the circle membrane. The value of the vibration frequency mode in theoretical are f01 = (200.6 ± 2.0) Hz, f11 = (319.7 ± 3.1) Hz, f21 = (428.5 ± 4.2) Hz. By using the Scilab program application, the results obtained show that the results frequency mode simulation f01, f11, dan f21 are similar to the normal mode in theoretical calculation. Thus, the simulation can be used to visualize waves of two dimensions in vibration and wave learning.